2010
DOI: 10.1007/s10096-010-1076-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clinically relevant viridans group streptococci by phenotypic and genotypic analysis

Abstract: 18 19Purpose: Two phenotypic and three molecular methods were assessed for their ability 20 to identify viridans group streptococci (VGS) to the species level. 21Methods: A panel of 23 clinical isolates, comprising strains isolated from infective 22 endocarditis, blood cultures, pleural and peritoneal fluid, and 19 type/reference strains 23 were analyzed. Identification was performed using two conventional phenotypic 24 methods, API ® rapid ID 32 Strep and VITEK ® 2 system; and genotypic analysis of the 25 nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 32 publications
1
46
0
1
Order By: Relevance
“…The housekeeping gene sodA has frequently been studied as a genotypic method for identifying VGS strains to the species level and has shown to be one of the most effective single-gene analyses, correctly identifying most VGS strains approximately 95% of the time (8-10, 19, 23). However, shortcomings in the ability of sodA sequencing to accurately resolve some S. mitis and S. oralis strains have been reported (3,(8)(9)(10)19). Thus, we next sought to determine how accurate sodA sequence analysis would be for our strains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The housekeeping gene sodA has frequently been studied as a genotypic method for identifying VGS strains to the species level and has shown to be one of the most effective single-gene analyses, correctly identifying most VGS strains approximately 95% of the time (8-10, 19, 23). However, shortcomings in the ability of sodA sequencing to accurately resolve some S. mitis and S. oralis strains have been reported (3,(8)(9)(10)19). Thus, we next sought to determine how accurate sodA sequence analysis would be for our strains.…”
Section: Resultsmentioning
confidence: 99%
“…The inherent problems with these approaches lie in the variability of traits within VGS species, poor reproducibility, subjectivity of interpretation, and the lack of availability of up-todate phenotypic information in the databases on more recently described or reevaluated species (7,8,10). Sequence analysis of the 16S rRNA gene has been utilized for VGS species-level identification; however, there is no agreement on a universal cutoff for species delineation (11).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in another study (11), 21 optochin-susceptible isolates were identified as S. mitis by multilocus sequence analysis (MLSA). Also, commercial biochemical test panels have limitations in identifying streptococci to the species level (12)(13)(14)(15)(16).…”
mentioning
confidence: 99%